Preoperative systemic immune-inflammation index may predict prolonged mechanical ventilation in patients with spontaneous basal ganglia intracerebral hemorrhage undergoing surgical operation - Xiao, Huaming; Li, Lei; Zhang, Feng; Cheng, Lei; Li, Yang; Han, Wenlan; Li, Huanting; Fan, Mingchao (Frontiers in Neurology, 2023)
Background: Prolonged mechanical ventilation (PMV) has been proven as a risk factor for poor outcomes in patients with neurocritical illness. Spontaneous basal ganglia intracerebral hemorrhage (ICH) is a common subtype of spontaneous hemorrhagic stroke, and is associated with high morbidity and mortality. Systemic immune-inflammation index (SII) as a novel comprehensive inflammatory index, and is associated with prognosis in various types critical illness. Objective: The aim of this study was to analyses the predictive value of preoperative SII for PMV in patients with spontaneous basal ganglia intracerebral hemorrhage (ICH) underwent surgical operation. Methods: This retrospective study was conducted in patients with hypertensive basal ganglia ICH underwent surgical operation between October 2014 and June 2021. SII was calculated using the following formula: SII = platelet counts×neutrophil counts/lymphocyte counts. Multivariate logistic regression analysis and receiver operating characteristics curve (ROC) were used to evaluate the potential risk factors of PMV after hypertensive ICH. Results: A total of 271 patients were enrolled. Of these, 112 patients (47.6%) presented PMV. Preoperative GCS (OR, 0.780; 95% CI, 0.688 - 0.883; P < 0.001), hematoma size (OR, 1.031; 95% CI, 1.016 - 1.047; P < 0.001), lactic acid (OR, 1.431; 95% CI, 1.015 - 2.017; P = 0.041) and SII (OR, 1.283; 95% CI, 1.049 - 1.568; P = 0.015) were significant risk factors for PMV in multivariate logistic regression. The corresponding area under the curves (AUC) of SII was 0.662 (95% CI, 0.595 - 0.729, P < 0.001), and the cutoff value was 2454.51. Conclusion: Preoperative SII may predict PMV in patients with spontaneous basal ganglia ICH underwent surgical operation.